Hinduism and the diaspora: a South African narrative - Kumar, P. Pratap (Rawat Publ., 2013)
Indians : a new community settles in South Africa -- A new religious tradition on the South African soil -- Consolidation of the tradition : temples and priesthood -- Centrality of ritual : temple and domestic practices -- Religious celebrations -- Goddess worship -- Community organisations, schools, rituals and language -- Some reflections on the major neo-Hindu organisations -- The Arya Samajists -- The Saiva Siddhantists -- The Ramakrishnaites -- The Divine Life Society -- The Hare Krishnas -- The Satya Sai Baba followers